Polymer-based copper ion imprinted chitosan adsorbent and preparation method thereof

By coating copper ion-imprinted chitosan with a polymer exhibiting good creep resistance and introducing a pore-forming agent, a three-dimensional porous network was constructed, which solved the problems of poor mechanical strength and easy loss of copper ion adsorbents, and achieved efficient adsorption and stable regeneration performance.

CN121016697APending Publication Date: 2025-11-28HEBEI UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511140467.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-14
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing copper ion adsorbents suffer from poor mechanical strength, difficulty in solid-liquid separation, and easy loss, leading to decreased mass transfer efficiency and insufficient cycle stability.

Method used

A polymer with excellent creep resistance, fracture toughness and solvent corrosion resistance was used as the coating material to coat copper ion imprinted chitosan. A pore-forming agent was introduced to construct a three-dimensional porous network architecture, optimize pore connectivity, and establish a concentration gradient-driven dual diffusion path.

Benefits of technology

It improves the mechanical integrity and recycling performance of copper ion-imprinted chitosan, achieving a balance between high adsorption capacity, rapid kinetics and cycling stability, and avoiding the decline in mass transfer efficiency caused by the reduction of specific surface area.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121016697A_ABST
    Figure CN121016697A_ABST
Patent Text Reader

Abstract

The invention provides a polymer-based copper ion imprinted chitosan adsorbent and a preparation method thereof. The preparation method comprises the following steps: mixing copper ion imprinted chitosan, a pore-forming agent and a polymer solution to obtain polymer gel; and dropwise adding the polymer gel into a cooling liquid, and solidifying to obtain the polymer-based copper ion imprinted chitosan adsorbent. A polymer with excellent creep resistance, fracture toughness and solvent corrosion resistance is adopted as a coating material to coat copper ion imprinted chitosan, and meanwhile, a pore forming agent is introduced, so that the polymer-based copper ion imprinted chitosan adsorbent with a three-dimensional porous network structure is constructed; the adsorbent is endowed with stable cyclic regeneration performance, and unification of high adsorption capacity, rapid dynamics and cyclic stability is realized.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of wastewater treatment, in particular to the removal of noble metal ions by adsorption, and more particularly to a polymer-based copper ion imprinted chitosan adsorbent and a preparation method thereof. BACKGROUND

[0002] Wastewater discharged from industrial processes such as metal smelting, battery production, and printing and dyeing often contains copper, causing serious water pollution and posing a great threat to human living environment and health. Methods for removing copper ions from wastewater mainly include membrane filtration, chemical precipitation, ion exchange, or electrochemical methods, but these methods have problems such as unsatisfactory removal effect, high treatment cost, and complex process flow. As an effective separation technology, adsorption has the advantages of high separation efficiency, simple operation, and easy recovery of separation products, and has a wide application prospect in the field of heavy metal ion wastewater treatment. Natural polymer chitosan has the advantages of wide source and biodegradability, and using it as a heavy metal ion adsorbent will not cause secondary pollution. However, ordinary chitosan is easily dissolved and lost in aqueous solution, especially in acidic aqueous solution, greatly limiting its application.

[0003] CN106064079A discloses a high-amine copper ion imprinted supported chitosan adsorbent material and a preparation process thereof. The material is prepared by first protecting the amine groups on chitosan with a mono-aldehyde substance, then cross-linking with epoxy chloropropane to obtain high-amine cross-linked chitosan, forming a complex with copper ions, and finally loading the high-amine cross-linked chitosan after complexation with an inorganic carrier. The high-amine copper ion imprinted supported chitosan adsorbent material provided by the invention has high selective adsorption capacity for copper ions.

[0004] CN112439392A discloses a carbon dioxide-responsive chitosan-based copper ion adsorbent material prepared by a photopolymerization method. The modified water-soluble chitosan with polymerizable double bonds is mixed uniformly with a photopolymerization monomer, a photoinitiator, a cross-linking agent, a cosolvent, and water, and then cured using a UV curing lamp. This cross-linked material achieves adsorption through the complexation of amino groups with copper ions. When carbon dioxide is introduced and responds with the primary amino group, the primary amino group forms an ammonium salt, losing the adsorption effect on copper ions, achieving desorption, and thus can be reused.

[0005] CN105964227A discloses a hyperbranched polyamide grafted chitosan adsorbent and its preparation and application, comprising loading an amino-terminated hyperbranched polyamide on chitosan to synthesize a solid-phase extraction material, introducing a large number of nitrogen-containing groups on chitosan to increase the content of active groups, and improving the adsorption performance of the adsorbent. The adsorbent is firmly bonded, stable in properties, good in reproducibility, and has a large enrichment factor. The adsorbent can be used for adsorption of heavy metal copper ions and dyes in environmental water samples.

[0006] Therefore, it is of great significance to provide an adsorbent with excellent adsorption and selectivity for copper ions and a preparation method thereof. SUMMARY

[0007] In view of the deficiencies of the prior art, the purpose of the present application is to provide a polymer-based copper ion imprinted chitosan adsorbent and a preparation method thereof. The present application aims to overcome the defects of poor mechanical strength, difficult solid-liquid separation and easy loss of copper ion adsorbents. A polymer with excellent anti-creep properties, fracture toughness and solvent corrosion resistance is used as a coating material to coat the copper ion imprinted chitosan, so as to maintain the mechanical integrity of the copper ion imprinted chitosan. At the same time, a pore-forming agent is introduced to construct a polymer-based copper ion imprinted chitosan adsorbent with a three-dimensional porous network architecture, thereby avoiding the problem of mass transfer efficiency decay caused by the reduction of specific surface area of the copper ion imprinted chitosan after coating the polymer. The adsorbent is endowed with stable cyclic regeneration performance, realizing the unity of high adsorption capacity, fast kinetics and cyclic stability.

[0008] To achieve the purpose of the present application, the following technical solutions are adopted:

[0009] In a first aspect, the present application provides a preparation method of a polymer-based copper ion imprinted chitosan adsorbent, comprising:

[0010] Mixing the copper ion imprinted chitosan, the pore-forming agent and the polymer solution to obtain a polymer gel; dropping the polymer gel into a cooling liquid to solidify, thereby obtaining the polymer-based copper ion imprinted chitosan adsorbent.

[0011] The application takes copper ion imprinted chitosan as the adsorption active material, is conducive to efficient adsorption and desorption cycle of copper ions, takes the polymer with excellent anti-creep characteristics, fracture toughness and solvent corrosion resistance as the coating material to coat the copper ion imprinted chitosan, effectively improves the mechanical integrity of the copper ion imprinted chitosan, and introduces the pore-forming agent, uses the polar end group in the molecular structure of the pore-forming agent, promotes the solute exchange between the coolant and the polymer gel through hydration, thereby establishing a concentration gradient driven double diffusion path, significantly optimizing the pore connectivity, and constructing the polymer-based copper ion imprinted chitosan adsorbent with a three-dimensional porous network architecture, avoiding the problem of mass transfer efficiency decay caused by the reduction of specific surface area of the copper ion imprinted chitosan after coating the polymer, and jointly giving the adsorbent stable cyclic regeneration performance, realizing the unity of high adsorption capacity, fast kinetics and cyclic stability.

[0012] Preferably, in the polymer solution, the polymer comprises polyvinylidene fluoride.

[0013] Preferably, in the polymer solution, the kind of solvent comprises any one or a combination of at least two of N,N-dimethylformamide, N,N-dimethylacetamide or N-methyl pyrrolidone.

[0014] Preferably, the kind of pore-forming agent comprises any one or a combination of at least two of sodium dodecyl sulfate, sodium dodecyl benzene sulfonate or Tween-80.

[0015] Preferably, the coolant comprises water and / or ice water mixture.

[0016] Preferably, the concentration of the polymer in the polymer solution is 50g / L-100g / L, for example, it can be 50g / L, 60g / L, 70g / L, 80g / L, 90g / L or 100g / L, including but not limited to the listed values, and other values not listed in the value range are also applicable.

[0017] Preferably, the mass ratio of the copper ion imprinted chitosan to the polymer in the polymer solution is (3-7):(7-3), for example, it can be 3:7, 4:6, 5:5, 6:4 or 7:3, including but not limited to the listed values, and other values not listed in the value range are also applicable.

[0018] Preferably, the mass of the pore-forming agent is 1wt%-4wt% of the mass of the polymer in the polymer solution, for example, it can be 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt% or 4wt%, including but not limited to the listed values, and other values not listed in the value range are also applicable.

[0019] Preferably, the preparation method of the copper ion imprinted chitosan comprises:

[0020] adding an initiator to the mixture of the copper ion template and the chitosan solution to obtain a first reaction solution; performing a grafting reaction on the first reaction solution to obtain a second reaction solution; adding a crosslinking agent to the second reaction solution, crosslinking and solidifying, and performing solid-liquid separation to obtain an intermediate; and eluting copper ions from the intermediate to obtain the copper ion imprinted chitosan; the solvent of the chitosan solution comprises water and an unsaturated carboxylic acid.

[0021] Preferably, the copper ion template comprises any one or a combination of at least two of copper sulfate, copper chloride, copper acetate or copper nitrate, and a typical but non-limiting combination includes a combination of copper sulfate and copper chloride, or a combination of copper acetate and copper nitrate, and preferably copper sulfate.

[0022] Preferably, the initiator comprises any one or a combination of at least two of potassium persulfate, ammonium persulfate or sodium bisulfite, and a typical but non-limiting combination includes a combination of potassium persulfate and ammonium persulfate, a combination of sodium bisulfite and potassium persulfate, or a combination of ammonium persulfate and sodium bisulfite.

[0023] Preferably, the crosslinking agent comprises glutaraldehyde.

[0024] Preferably, the unsaturated carboxylic acid comprises any one or a combination of at least two of acrylic acid, itaconic acid or maleic acid, and a typical but non-limiting combination includes a combination of acrylic acid and itaconic acid, a combination of maleic acid and acrylic acid, or a combination of itaconic acid and maleic acid.

[0025] Preferably, the volume ratio of water to unsaturated carboxylic acid is (35-70):1, and for example, can be 30:1, 40:1, 45:1, 50:1, 55:1, 60:1, 65:1 or 70:1, including but not limited to the listed values, and other values not listed within the value range are also applicable.

[0026] Preferably, in the chitosan solution, the mass concentration of chitosan is 10g / L-20g / L, and for example, can be 10g / L, 11g / L, 12g / L, 13g / L, 14g / L, 15g / L, 16g / L, 17g / L, 18g / L, 19g / L or 20g / L, including but not limited to the listed values, and other values not listed within the value range are also applicable.

[0027] Preferably, in the first reaction solution, the mass concentration of copper ions is 0.25g / L-1.35g / L, and for example, can be 0.25g / L, 0.45g / L, 0.65g / L, 0.85g / L, 1.05g / L, 1.15g / L, 1.25g / L or 1.35g / L, including but not limited to the listed values, and other values not listed within the value range are also applicable.

[0028] Preferably, the mass concentration of initiator in the first reaction solution is 4.5 g / L to 10 g / L, for example, it can be 4.5 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L or 10 g / L, including but not limited to the listed values, other values not listed in the value range are also applicable.

[0029] Preferably, the grafting reaction includes a first grafting reaction and a second grafting reaction; the temperature of the first grafting reaction is higher than that of the second grafting reaction.

[0030] Preferably, the temperature of the first grafting reaction is 70°C to 90°C, for example, it can be 70°C, 75°C, 80°C, 85°C or 90°C, including but not limited to the listed values, other values not listed in the value range are also applicable.

[0031] Preferably, the time of the first grafting reaction is 15 min to 60 min, for example, it can be 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, including but not limited to the listed values, other values not listed in the value range are also applicable.

[0032] Preferably, the temperature of the second grafting reaction is 50°C to 70°C, for example, it can be 50°C, 55°C, 60°C, 65°C or 70°C, including but not limited to the listed values, other values not listed in the value range are also applicable.

[0033] Preferably, the time of the second grafting reaction is 40 min to 90 min, for example, it can be 40 min, 50 min, 60 min, 70 min, 80 min or 90 min, including but not limited to the listed values, other values not listed in the value range are also applicable.

[0034] Preferably, the grafting reaction is carried out under an inert atmosphere, and the inert atmosphere includes nitrogen and / or an inert gas.

[0035] Preferably, the inert gas includes any one or a combination of at least two of helium, neon or argon.

[0036] Preferably, the volume ratio of the crosslinking agent to the second reaction solution is 1:(95 to 300), for example, it can be 1:95, 1:100, 1:125, 1:150, 1:175, 1:200, 1:225, 1:250, 1:275 or 1:300, including but not limited to the listed values, other values not listed in the value range are also applicable.

[0037] Preferably, the temperature of the cross-linking solidification is 35-55°C, such as 35°C, 40°C, 45°C, 50°C or 55°C, including but not limited to the listed values, and other values within the range of values are also applicable.

[0038] Preferably, the time of the cross-linking solidification is 1-3h, such as 1h, 1.5h, 2h, 2.5h or 3h, including but not limited to the listed values, and other values within the range of values are also applicable.

[0039] Preferably, the method of solid-liquid separation comprises centrifugation.

[0040] Preferably, the method further comprises washing and drying the intermediate using water and ethanol, respectively.

[0041] Preferably, the method of washing comprises centrifugation.

[0042] Preferably, the temperature of the drying is 50-80°C, such as 50°C, 60°C, 70°C or 80°C, including but not limited to the listed values, and other values within the range of values are also applicable. The time of the drying is not specifically limited, and is aimed at complete evaporation of residual solvent.

[0043] As a preferred technical solution of the present application, the method of elution comprises mixing the intermediate with a template removal agent solution to elute the copper ions in the intermediate.

[0044] Preferably, in the template removal agent solution, the template removal agent comprises any one or a combination of at least two of disodium ethylenediaminetetraacetate, dilute hydrochloric acid, dilute sulfuric acid or dilute nitric acid, and typical but non-limiting combinations include a combination of disodium ethylenediaminetetraacetate and dilute hydrochloric acid, or a combination of dilute sulfuric acid and dilute nitric acid.

[0045] Preferably, the concentration of the template removal agent solution is 0.05-0.25mol / L, such as 0.05mol / L, 0.1mol / L, 0.15mol / L, 0.2mol / L or 0.25mol / L, including but not limited to the listed values, and other values within the range of values are also applicable.

[0046] Preferably, the solid-liquid ratio of the intermediate to the template removal agent solution is 0.5-2g / L, such as 0.5g / L, 0.75g / L, 1g / L, 1.25g / L, 1.5g / L, 1.75g / L or 2g / L, including but not limited to the listed values, and other values within the range of values are also applicable.

[0047] Preferably, the elution time is 2h to 10h, for example, it can be 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h, including but not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0048] Preferably, the preparation method further includes washing, drying and grinding the copper ion-imprinted chitosan.

[0049] Preferably, the washing method includes centrifugal washing using water and ethanol respectively.

[0050] In a second aspect, the present invention provides a polymer-based copper ion-imprinted chitosan adsorbent, which is prepared by the preparation method described in the first aspect.

[0051] Compared with the prior art, the present invention has the following beneficial effects:

[0052] This invention uses copper-imprinted chitosan as the adsorbent active material, which is beneficial for the efficient adsorption and desorption cycle of copper ions. A polymer with excellent creep resistance, fracture toughness, and solvent corrosion resistance is used as the coating material to coat the copper-imprinted chitosan, effectively improving its mechanical integrity. Simultaneously, a pore-forming agent is introduced. Utilizing the polar end groups in the pore-forming agent's molecular structure, hydration promotes solute exchange between the coolant and the polymer gel. The concentration gradient-driven dual diffusion pathway significantly optimizes pore connectivity, resulting in a polymer-based copper-imprinted chitosan adsorbent with a three-dimensional porous network architecture. This avoids the problem of mass transfer efficiency degradation caused by the reduction in the specific surface area of ​​copper-imprinted chitosan after polymer coating. Together, these factors endow the adsorbent with stable cyclic regeneration performance, achieving a balance between high adsorption capacity, rapid kinetics, and cyclic stability. Attached Figure Description

[0053] Figure 1 This is a SEM image of the surface of the polymer-based copper ion-imprinted chitosan adsorbent in Example 1.

[0054] Figure 2 This is a SEM image of the cross-section of the polymer-based copper ion-imprinted chitosan adsorbent in Example 1.

[0055] Figure 3 This is a SEM image of the cross-section of the polymer-based copper ion-imprinted chitosan adsorbent in Example 1.

[0056] Figure 4 This is a SEM image of the surface of the copper ion-imprinted chitosan adsorbent in Comparative Example 2. Detailed Implementation

[0057] The technical solutions of the present application will be further illustrated by specific embodiments. Those skilled in the art should understand that the embodiments are only used to help understand the present application, and should not be regarded as specific limitations on the present application.

[0058] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of this application; the use of the terms "including," "comprising," "having" and variations thereof herein is intended to be broad and encompass the terms "consisting of" and "consisting essentially of."

[0059] In the description of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "a plurality of" is two or more, unless otherwise explicitly specified.

[0060] In one specific embodiment, the present application provides a preparation method of a polymer-based copper ion imprinted chitosan adsorbent, the preparation method comprising:

[0061] (1) preparing copper ion imprinted chitosan: adding an initiator into a mixed solution of a copper ion template and a chitosan solution to obtain a first reaction solution, the solvent of the chitosan solution comprising water and an unsaturated carboxylic acid in a volume ratio of (35-70):1, the mass concentration of chitosan in the chitosan solution being 10 g / L-20 g / L, the mass concentration of copper ions in the first reaction solution being 0.25 g / L-1.35 g / L, and the mass concentration of the initiator being 4.5 g / L-10 g / L; performing a grafting reaction on the first reaction solution under an inert atmosphere, the grafting reaction comprising first incubating at 70℃-90℃ for 15 min-60 min, and then incubating at 50℃-70℃ for 40 min-90 min to complete the grafting reaction, thereby obtaining a second reaction solution; adding a crosslinking agent into the second reaction solution, the volume ratio of the crosslinking agent to the second reaction solution being 1:(95-300), crosslinking and solidifying at 35℃-55℃ for 1 h-3 h, centrifugal separation, washing the intermediate with water and ethanol respectively, and vacuum drying at 50℃-80℃; mixing the intermediate with a template removal agent solution with a concentration of 0.05 mol / L-0.25 mol / L according to a solid-liquid ratio of 0.5 g / L-2 g / L, stirring and eluting for 2 h-10 h to elute the copper ions in the intermediate, thereby obtaining the copper ion imprinted chitosan, and washing, drying and grinding the copper ion imprinted chitosan.

[0062] (2) Preparing the polymer-based copper ion imprinted chitosan adsorbent: mixing the copper ion imprinted chitosan prepared in step (1), a pore-forming agent and a polymer solution with a concentration of 50 g / L-100 g / L to obtain a polymer gel; wherein the mass ratio of the copper ion imprinted chitosan to the polymer in the polymer solution is (3-7):(7-3), and the mass of the pore-forming agent is 1wt%-4wt% of the mass of the polymer in the polymer solution; dropping the polymer gel into a cooling liquid to solidify, thereby obtaining the polymer-based copper ion imprinted chitosan adsorbent.

[0063] In some embodiments, the unsaturated carboxylic acid comprises any one of acrylic acid, itaconic acid or maleic acid, or a combination of at least two thereof, typically but not limitedly a combination of acrylic acid and itaconic acid, a combination of maleic acid and acrylic acid, or a combination of itaconic acid and maleic acid.

[0064] In some embodiments, in the polymer solution, the polymer comprises polyvinylidene fluoride.

[0065] In some embodiments, in the polymer solution, the solvent comprises any one of N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone, or a combination of at least two thereof, typically but not limitedly a combination of N,N-dimethylformamide and N,N-dimethylacetamide, or a combination of N-methylpyrrolidone and N,N-dimethylformamide.

[0066] In some embodiments, the pore-forming agent comprises any one of sodium dodecyl sulfate, sodium dodecyl benzene sulfonate or Tween-80, or a combination of at least two thereof, typically but not limitedly a combination of sodium dodecyl sulfate and sodium dodecyl benzene sulfonate, or a combination of Tween-80 and sodium dodecyl sulfate.

[0067] In some embodiments, the cooling liquid comprises water and / or an ice-water mixture.

[0068] The application takes copper ion imprinted chitosan as an adsorption active material, which is beneficial to efficient adsorption and desorption cycle of copper ions, and the copper ion imprinted chitosan is coated by using a polymer with excellent anti-creep characteristics, fracture toughness and solvent corrosion resistance as a coating material, which effectively improves the mechanical integrity of the copper ion imprinted chitosan, and a pore-forming agent is introduced, the polar end groups in the molecular structure of the pore-forming agent are used to promote the solute exchange between the coolant and the polymer gel through hydration, thereby establishing a concentration gradient driven double diffusion path, which significantly optimizes the connectivity of the pores, and a polymer-based copper ion imprinted chitosan adsorbent with a three-dimensional porous network architecture is constructed, which avoids the problem of mass transfer efficiency decay caused by the reduction of specific surface area of the copper ion imprinted chitosan after coating the polymer, and the adsorbent is endowed with stable cyclic regeneration performance, realizing the unity of high adsorption capacity, fast kinetics and cyclic stability.

[0069] In the application, the copper ion imprinted chitosan is prepared by a specific preparation method, the spatial configuration of the functional groups is fixed by using a copper ion template agent, specific recognition sites are formed, and the adsorption selectivity and capacity of the polymer-based copper ion imprinted chitosan adsorbent prepared by using the copper ion imprinted chitosan as a raw material for copper ions are significantly improved. At the same time, the use of the crosslinking agent can enhance the structural stability of the copper ion imprinted chitosan, reduce the steric hindrance of the active sites, and improve the regeneration performance of the copper ion imprinted chitosan. Through the reaction of chitosan and crosslinking agent induced by the copper ion template agent, and then eluting to form the imprinting cavity, efficient adsorption and desorption cycle of copper ions can be realized.

[0070] In the application, the solvent for the chitosan solution includes an unsaturated carboxylic acid, which provides a suitable acidic environment for the protonation of chitosan, promotes the protonation of chitosan, and forms hydrogen bonds between the carboxylic acid groups and the hydroxyl or amino groups of chitosan, further promoting the dispersion of chitosan. Under the action of the subsequent initiator, the unsaturated carboxylic acid monomer realizes the grafting modification of chitosan, thereby introducing a large number of carboxyl groups on the chitosan chain. The three-dimensional network composed of chitosan main chain and unsaturated carboxylic acid polymer side chain enhances the coordination ability to metal ions.

[0071] In some embodiments, the copper ion template agent includes any one or a combination of at least two of copper sulfate, copper chloride, copper acetate or copper nitrate, typical but non-limiting combinations include a combination of copper sulfate and copper chloride, or a combination of copper acetate and copper nitrate, preferably copper sulfate.

[0072] In some embodiments, the initiator includes any one or a combination of at least two of potassium persulfate, ammonium persulfate or sodium bisulfite, typical but non-limiting combinations include a combination of potassium sulfate and ammonium persulfate, a combination of sodium bisulfite and potassium sulfate, or a combination of ammonium persulfate and sodium bisulfite.

[0073] In some embodiments, the cross-linking agent comprises glutaraldehyde.

[0074] In some embodiments, the inert atmosphere comprises nitrogen and / or an inert gas.

[0075] In some embodiments, the inert gas comprises any one or a combination of at least two of helium, neon, or argon.

[0076] In the present application, the template removal agent is selected from a material with strong coordination ability. The template removal agent can bind with copper ions preferentially through chelation competition, break the coordination bond with the polymer, form a water-soluble complex, and separate from the three-dimensional network composed of the chitosan main chain and the unsaturated carboxylic acid polymer side chain.

[0077] In some embodiments, the template removal agent in the template removal agent solution comprises any one or a combination of at least two of disodium ethylenediaminetetraacetate, dilute hydrochloric acid, dilute sulfuric acid, or dilute nitric acid. A typical but non-limiting combination comprises a combination of disodium ethylenediaminetetraacetate and dilute hydrochloric acid, or a combination of dilute sulfuric acid and dilute nitric acid.

[0078] In another specific embodiment, the present application provides a polymer-based copper ion imprinted chitosan adsorbent prepared by the preparation method described in the aforementioned specific embodiment.

[0079] Example 1

[0080] The present embodiment provides a preparation method of a polymer-based copper ion imprinted chitosan adsorbent, which comprises:

[0081] (1) Preparing copper ion imprinted chitosan: adding potassium persulfate into a mixture solution of copper sulfate and chitosan solution to obtain a first reaction solution, the solvent of the chitosan solution is water and acrylic acid with a volume ratio of 56:1, the mass concentration of chitosan in the chitosan solution is 14 g / L, in the first reaction solution, the mass concentration of copper ions is 0.8 g / L, and the mass concentration of potassium persulfate is 5.6 g / L; under a nitrogen atmosphere, first heat the first reaction solution to 80°C and keep for 30 min, and then keep at 60°C for 60 min to complete the grafting reaction to obtain a second reaction solution; adding 50vol% glutaraldehyde aqueous solution into the second reaction solution, the volume ratio of glutaraldehyde in the 50% glutaraldehyde aqueous solution to the second reaction solution is 1:145, crosslinking and solidifying at 40°C for 2 h, centrifugal separation, washing the intermediate with water and ethanol respectively for 3 times, and vacuum drying at 60°C; mixing the intermediate with an ethylenediaminetetraacetic acid disodium solution with a concentration of 0.1 mol / L according to a solid-liquid ratio of 1 g / L, stirring and eluting for 2 h to elute copper ions in the intermediate, obtaining the polymer-based copper ion imprinted chitosan adsorbent, and washing, drying and grinding the copper ion imprinted chitosan.

[0082] (2) Preparing the polymer-based copper ion imprinted chitosan adsorbent: mixing the copper ion imprinted chitosan prepared in step (1), sodium dodecyl sulfate and polyvinylidene fluoride N,N-dimethylformamide with a concentration of 80 g / L to obtain a polymer gel, wherein the mass ratio of copper ion imprinted chitosan to polyvinylidene fluoride is 5:5, and the mass of sodium dodecyl sulfate is 3wt% of polyvinylidene fluoride; dropping the polymer gel into water drop by drop using a syringe to obtain the polymer-based copper ion imprinted chitosan adsorbent by solidification.

[0083] Example 2

[0084] The embodiment provides a preparation method of a polymer-based copper ion imprinted chitosan adsorbent, the preparation method comprising:

[0085] (1) The copper ion imprinted chitosan is prepared as follows: potassium persulfate is added into a mixture of copper chloride and chitosan solution to obtain a first reaction solution, the solvent of the chitosan solution is water and acrylic acid in a volume ratio of 35:1, the mass concentration of chitosan in the chitosan solution is 10 g / L, the mass concentration of copper ions in the first reaction solution is 0.25 g / L, and the mass concentration of potassium persulfate in the first reaction solution is 4.5 g / L; under an inert atmosphere, the first reaction solution is first heated to 70°C and kept for 15 min, and then kept at 50°C for 40 min to complete the grafting reaction, thereby obtaining a second reaction solution; 50vol% glutaraldehyde aqueous solution is added into the second reaction solution, the volume ratio of glutaraldehyde to the second reaction solution in the 50vol% glutaraldehyde aqueous solution is 1:300, and the mixture is crosslinked and solidified at 35°C for 1 h, and then centrifuged to obtain an intermediate, which is washed with water and ethanol respectively and dried at 50°C under vacuum; the intermediate is mixed with an ethylenediaminetetraacetic acid disodium salt solution with a concentration of 0.05 mol / L at a solid-liquid ratio of 0.5 g / L, and stirred for 5 h to elute the copper ions in the intermediate, thereby obtaining the polymer-based copper ion imprinted chitosan adsorbent, and the copper ion imprinted chitosan is washed, dried and ground.

[0086] (2) The polymer-based copper ion imprinted chitosan adsorbent is prepared as follows: the copper ion imprinted chitosan, sodium dodecyl sulfate and polyvinylidene fluoride N,N-dimethylformamide with a concentration of 50 g / L prepared in step (1) are mixed to obtain a polymer gel, wherein the mass ratio of the copper ion imprinted chitosan to the polyvinylidene fluoride is 3:7, and the mass of the sodium dodecyl sulfate is 1wt% of the polyvinylidene fluoride; the polymer gel is dropped into water drop by drop using a syringe, and the polymer-based copper ion imprinted chitosan adsorbent is obtained by solidification.

[0087] Example 3

[0088] The embodiment provides a preparation method of a polymer-based copper ion imprinted chitosan adsorbent, and the preparation method comprises the following steps:

[0089] (1) Preparation of copper ion imprinted chitosan: potassium persulfate is added to a mixture of copper nitrate and chitosan solution to obtain a first reaction solution, the solvent of the chitosan solution is water and maleic acid in a volume ratio of 70:1, the mass concentration of chitosan in the chitosan solution is 20 g / L, in the first reaction solution, the mass concentration of copper ions is 1.35 g / L, and the mass concentration of potassium persulfate is 10 g / L; under an inert atmosphere, the first reaction solution is first heated to 90℃ for 60 min, and then heated at 70℃ for 90 min to complete the grafting reaction to obtain a second reaction solution; 50vol% glutaraldehyde aqueous solution is added to the second reaction solution, the volume ratio of glutaraldehyde to the second reaction solution in the 50vol% glutaraldehyde aqueous solution is 1:95, and crosslinking and solidification is carried out at 55℃ for 3h, centrifugal separation is carried out, the intermediate is washed with water and ethanol respectively, and vacuum drying is carried out at 80℃; the intermediate is mixed with an ethylenediaminetetraacetic acid disodium solution with a concentration of 0.25 mol / L according to a solid-liquid ratio of 2 g / L, stirring elution is carried out for 10h to elute copper ions in the intermediate to obtain the polymer-based copper ion imprinted chitosan adsorbent, and the copper ion imprinted chitosan is washed, dried and ground.

[0090] (2) Preparation of polymer-based copper ion imprinted chitosan adsorbent: the copper ion imprinted chitosan, sodium dodecyl sulfate and polyvinylidene fluoride N,N-dimethylformamide with a concentration of 100 g / L obtained in step (1) are mixed to obtain a polymer gel, wherein the mass ratio of copper ion imprinted chitosan to polyvinylidene fluoride is 7:3, and the mass of sodium dodecyl sulfate is 4wt% of polyvinylidene fluoride; the polymer gel is dropped into water drop by drop using a syringe, and the polymer-based copper ion imprinted chitosan adsorbent is obtained by solidification.

[0091] Example 4

[0092] The embodiment provides a preparation method of a polymer-based copper ion imprinted chitosan adsorbent, which is the same as that in example 1, except that the pore-forming agent in step (2) is replaced by an equal amount of sodium dodecylbenzenesulfonate.

[0093] Example 5

[0094] The embodiment provides a preparation method of a polymer-based copper ion imprinted chitosan adsorbent, which is the same as that in example 1, except that the pore-forming agent in step (2) is replaced by an equal amount of Tween-80.

[0095] Example 6

[0096] The embodiment provides a preparation method of a polymer-based copper ion imprinted chitosan adsorbent, which is same as that in the embodiment 1, except that the mass of sodium dodecyl sulfate in the step (2) is 5% of the mass of the polyvinylidene fluoride.

[0097] Embodiment 7

[0098] The embodiment provides a preparation method of a polymer-based copper ion imprinted chitosan adsorbent, which is same as that in the embodiment 1, except that the mass of sodium dodecyl sulfate in the step (2) is 5% of the mass of the polyvinylidene fluoride.

[0099] Embodiment 8

[0100] The embodiment provides a preparation method of a polymer-based copper ion imprinted chitosan adsorbent, which is same as that in the embodiment 1, except that the mass ratio of the copper ion imprinted chitosan to the polyvinylidene fluoride in the step (2) is 2:8.

[0101] Embodiment 9

[0102] The embodiment provides a preparation method of a polymer-based copper ion imprinted chitosan adsorbent, which is same as that in the embodiment 1, except that the mass ratio of the copper ion imprinted chitosan to the polyvinylidene fluoride in the step (2) is 8:2.

[0103] Embodiment 10

[0104] The embodiment provides a preparation method of a polymer-based copper ion imprinted chitosan adsorbent, which is same as that in the embodiment 1, except that the mass concentration of the potassium sulfate in the first reaction solution in the step (1) is 3.5g / L.

[0105] Embodiment 11

[0106] The embodiment provides a preparation method of a polymer-based copper ion imprinted chitosan adsorbent, which is same as that in the embodiment 1, except that the mass concentration of the potassium sulfate in the first reaction solution in the step (1) is 12g / L.

[0107] Embodiment 12

[0108] The embodiment provides a preparation method of a polymer-based copper ion imprinted chitosan adsorbent, which is same as that in the embodiment 1, except that the volume ratio of the glutaraldehyde to the second reaction solution in the step (1) is 1:90.

[0109] Embodiment 13

[0110] The embodiment provides a preparation method of a polymer-based copper ion imprinted chitosan adsorbent, which is the same as that in the embodiment 1, with the exception that the volume ratio of glutaraldehyde to the second reaction solution in step (1) is 1:310.

[0111] Comparative example 1

[0112] The comparative example provides a preparation method of a copper ion imprinted chitosan adsorbent, which is the same as that in the embodiment 1, with the exception that step (2) is not performed.

[0113] Comparative example 2

[0114] The comparative example provides a preparation method of a polymer-based copper ion imprinted chitosan adsorbent, which is the same as that in the embodiment 1, with the exception that sodium dodecyl sulfate is not added in step (2).

[0115] Performance test:

[0116] The surface of the adsorbents prepared in the embodiment 1 and the comparative example 2 is subjected to SEM test, and the test results are shown in Figs. 1 and 2. Figure 1 and Figure 4 The cross section of the polymer-based copper ion imprinted chitosan adsorbent prepared in the embodiment 1 is subjected to SEM test, and the test results are shown in Figs. 3 and 4. Figure 2 and Figure 3 .

[0117] Nickel ions with a radius close to that of copper ions are used as interference ions to test the selectivity of the polymer-based copper ion imprinted chitosan adsorbent to copper ions, and the test method is as follows:

[0118] Copper ion and nickel ion solutions with a concentration of 50 mg / L are used as adsorption samples, and the adsorbents provided in all the above examples and comparative examples are added in a solid-liquid ratio of 0.4 g / L to test the selectivity of the adsorbents to copper ions, and the selectivity factor is calculated, and the test results are shown in Table 1.

[0119] 0.1 mol / L of ethylenediaminetetraacetic acid disodium solution is used to desorb the adsorbents after adsorbing copper ions in all the above examples and comparative examples, and the desorption rate is tested; and the adsorbents are subjected to 10 times of adsorption and desorption, and the adsorption rate and the desorption rate in the 10th test are shown in Table 1.

[0120] In the above test process, atomic absorption spectrophotometry is used to determine the ion concentration in the solution, and C0(mg / L) and C e (mg / L) are used to represent the initial concentration and the equilibrium concentration, V(L) represents the volume of the sample solution to be adsorbed, m(g) represents the mass of the adsorbent, C d (mg / L) represents the concentration of the ethylenediaminetetraacetic acid disodium solution, V d(L) represents the volume of ethylenediaminetetraacetic acid disodium solution, and the equilibrium adsorption capacity q is calculated according to the following formulas 1-5 e , the metal ion distribution coefficient K d , the Cu / Ni selection factor a Cu / Ni , the adsorption rate E and the desorption rate DE.

[0121] q e = (C0-Ce) / m Formula 1

[0122] K d = q e / Ce Formula 2

[0123] a Cu / Ni = K d (Cu) / K d (Ni) Formula 3

[0124] E = (C0-Ce) / C0 Formula 4

[0125] DE = C d V d / ((C0-C e ) / V) Formula 5

[0126] Table 1

[0127]

[0128] According to the test results of Examples 1-3 and Comparative Example 1 in Table 1, the present application uses a polymer with excellent anti-creep properties, fracture toughness and solvent corrosion resistance as a coating material to coat the copper ion imprinted chitosan, and introduces a pore-forming agent to construct a polymer-based copper ion imprinted chitosan adsorbent with a three-dimensional porous network architecture, effectively improving the mechanical integrity of the copper ion imprinted chitosan, and avoiding the problem of mass transfer efficiency decay caused by the reduction of specific surface area of the copper ion imprinted chitosan after coating the polymer. As shown in the cross-sectional view of the polymer-based copper ion imprinted chitosan adsorbent prepared in Example 1 Figure 2 , the inside of the adsorbent is full, and as shown in the partial enlarged view Figure 3 , the wire-shaped polymer matrix and the cluster-shaped copper ion imprinted chitosan together construct a three-dimensional porous network architecture, which together endows the adsorbent with stable cyclic regeneration performance, realizing the unity of high adsorption capacity, fast kinetics and cyclic stability.

[0129] According to the test results of Example 1 and Comparative Example 2, if no pore-forming agent is added, the three-dimensional porous network architecture cannot be effectively constructed, and the connectivity of the pores cannot be improved, as compared with Figure 1 and Figure 4The polymer-based copper ion imprinted chitosan adsorbent prepared by introducing the pore-forming agent in embodiment 1 has a rich pore on the surface, which is beneficial to the diffusion of solutes from the surface of the microspheres to the inside of the microspheres, while the polymer-based copper ion imprinted chitosan adsorbent prepared without adding the pore-forming agent in comparative example 1 has a dense surface, which is not conducive to the diffusion of solutes.

[0130] According to the test results of embodiments 1, 6 and 7, if the amount of the pore-forming agent is too small, the pore-forming is not complete, and a complete three-dimensional network structure cannot be effectively constructed, and if the amount of the pore-forming agent is too large, part of the pore structure may collapse, causing the copper ion imprinted chitosan in the core to leak, resulting in poor adsorption effect.

[0131] According to the test results of embodiments 1, 8 and 9, if the mass ratio of the copper ion imprinted chitosan to the polymer is too small, that is, the mass proportion of the copper ion imprinted chitosan is too small, it is not conducive to the uniform distribution of the copper ion imprinted chitosan in the polymer matrix, and if the mass ratio of the copper ion imprinted chitosan to the polymer is too large, that is, the mass proportion of the copper ion imprinted chitosan is too large, the copper ion imprinted chitosan powders will agglomerate, which will cause the effective specific surface area to decrease significantly, and all of these will result in poor adsorption effect.

[0132] According to the test results of embodiments 1, 10 and 11, if the amount of potassium persulfate is too small, it will be difficult for the acrylic acid to completely polymerize, and if the amount of potassium persulfate is too large, the polymerization will be excessive, resulting in poor selectivity of copper ions.

[0133] According to the test results of embodiments 1, 12 and 13, if the amount of the crosslinking agent is too small or too large, the copper ion imprinted binding sites in the three-dimensional crosslinked network are too loose or too tight, resulting in poor selective adsorption performance of copper ions.

[0134] The applicant declares that the above description is only a specific embodiment of the present application, but the protection scope of the present application is not limited thereto, and those skilled in the art should understand that any changes or replacements within the technical scope disclosed by the present application can be easily thought of by those skilled in the art, and all of these fall within the protection scope and disclosure scope of the present application.

Claims

1. A method for preparing a polymer-based copper ion-imprinted chitosan adsorbent, characterized in that, The preparation method includes: A polymer gel is obtained by mixing copper ion-imprinted chitosan, a pore-forming agent, and a polymer solution; the polymer gel is then dropped into a cooling liquid and solidified to obtain the polymer-based copper ion-imprinted chitosan adsorbent.

2. The preparation method according to claim 1, characterized in that, The polymer solution contains polyvinylidene fluoride; And / or, in the polymer solution, the solvent includes any one or a combination of at least two of N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone; And / or, the pore-forming agent includes any one or a combination of at least two of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, or Tween-80; And / or, the coolant comprises water and / or a mixture of ice and water.

3. The preparation method according to claim 1 or 2, characterized in that, The concentration of the polymer in the polymer solution is 50 g / L to 100 g / L; And / or, the mass ratio of the copper ion-imprinted chitosan to the polymer in the polymer solution is (3-7):(7-3); And / or, the mass of the pore-forming agent is 1 wt% to 4 wt% of the polymer mass in the polymer solution.

4. The preparation method according to any one of claims 1 to 3, characterized in that, The preparation method of the copper ion-imprinted chitosan includes: An initiator is added to a mixture of copper ion template agent and chitosan solution to obtain a first reaction solution; a grafting reaction is performed on the first reaction solution to obtain a second reaction solution; a crosslinking agent is added to the second reaction solution, crosslinking and curing are performed, and solid-liquid separation is carried out to obtain an intermediate; copper ions are eluted from the intermediate to obtain the copper ion imprinted chitosan. The solvent for the chitosan solution includes water and unsaturated carboxylic acids.

5. The preparation method according to claim 4, characterized in that, The copper ion template agent includes any one or a combination of at least two of copper sulfate, copper chloride, copper acetate or copper nitrate. And / or, the initiator includes any one or a combination of at least two of potassium persulfate, ammonium persulfate, or sodium bisulfite; And / or, the crosslinking agent includes glutaraldehyde; And / or, the unsaturated carboxylic acid includes any one or a combination of at least two of acrylic acid, itaconic acid, or maleic acid; And / or, the volume ratio of water to unsaturated carboxylic acid is (35-70):1; And / or, the volume ratio of the crosslinking agent to the second reaction solution is 1:(95-300); And / or, the crosslinking curing temperature is 35℃~55℃; And / or, the crosslinking curing time is 1h to 3h.

6. The preparation method according to claim 4 or 5, characterized in that, The grafting reaction includes a first grafting reaction and a second grafting reaction; the temperature of the first grafting reaction is higher than that of the second grafting reaction. And / or, the grafting reaction is carried out under an inert atmosphere.

7. The preparation method according to claim 6, characterized in that, The temperature of the first grafting reaction is 70℃~90℃; And / or, the time for the first grafting reaction is 15 min to 60 min; And / or, the temperature of the second grafting reaction is 50°C to 70°C; And / or, the second grafting reaction takes 40 min to 90 min.

8. The preparation method according to any one of claims 4 to 7, characterized in that, The elution method includes mixing the intermediate with a template removal agent solution to elute copper ions from the intermediate.

9. The preparation method according to claim 8, characterized in that, The template removal agent solution includes any one or a combination of at least two of the following: disodium ethylenediaminetetraacetate, dilute hydrochloric acid, dilute sulfuric acid, or dilute nitric acid; And / or, the concentration of the template removal agent solution is 0.05 mol / L to 0.25 mol / L; And / or, the solid-liquid ratio of the intermediate to the template removal agent solution is 0.5 g / L to 2 g / L; And / or, the elution time is 2h to 10h.

10. A polymer-based copper ion-imprinted chitosan adsorbent, characterized in that, The polymer-based copper ion-imprinted chitosan adsorbent is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Hyperbranched polyamide-grafted chitosan adsorbent and its preparation method and use

    CN105964227A

  • High-amine Copper Ion-Impressed Supported Chitosan Adsorbent Material and Its Preparation Process

    CN106064079A

  • Carbon dioxide responsive chitosan-based copper ion adsorbing material prepared by photopolymerization method

    CN112439392A